Электрофизическая модель эмульсии типа минеральное масло – вода инженерного типа - Рудаков, Валерий Васильевич; Коробко, Анатолий Иванович; Коробко, А. А. (НТУ "ХПИ", 2009)
В статті розглянуті питання щодо визначення кількості води в системі мінеральне масло – вода діелектричним методом. Також наведена теоретична модель, яка описує принцип дії даного пристрою.

In the article the considered questions are in relation to determining the amount of water in the mixes mineral oil – water by a dielectric method. A theoretical model which describes principle of action of this device is also considered.
Keywords: диэлектрический метод; топливные масла; влагосодержание; проницаемость